Some Freinet ideas for education - Silva, Carla Nayelli Terra; Cunha, Carolina Rodrigues (Revista Hipótese, 2015)
This article shows Freinet ideas to revolutionize published school, prioritizing students, being totally the opposite from the traditional methods.We expounded the techniques made for Freinet at the turn of the century XX, to list to education applied on high school currently, proposing execute some of your techniques in classroom. We noticed that Freinet methods is innovator even if it was raised a long time ago and it is totally viable to use to get some satisfactory results.
Keywords: Freinet; Education; High School; Physics